ANALISIS SARANA PRASARANA TERHADAP KEPUASAN WISATAWAN BERDAMPAK KEPADA MINAT BERKUNJUNG KEMBALI KE JEMBATAN BARELANG - Rosie Oktavia Puspita Rini; Agung Edy Wibowo (JURNAL MATA PARIWISATA, 2022)
This study aims to determine whether the variables of Facilities and Infrastructure partially influence the Interest in Returning. Moderating variable with Tourist Satisfaction in moderating the relationship between Facilities and Infrastructure on Return Interest. This research was conducted in the Barelang bridge area, Batam. By taking the research subject of tourists who have visited again. Data collection was carried out by distributing questionnaires. The analysis method uses the Structural Equation Model (SEM) using the WarpPLS 7.0 software. The results of the partial test of each independent variable on the dependent variable and the moderating variable. Partial test results show that Sarana has a positive and significant effect on tourist decisions. Infrastructure has a positive and significant effect on tourist decisions. The residual test shows that Tourist Satisfaction is a moderating variable that is only able to strengthen the influence of Means on Revisit Interest. The results of the research using the residual test show that Tourist Satisfaction is a moderating variable that is able to strengthen The influence of Infrastructure on revisit interest.